DIEP Flap for Head and Neck Reconstruction: An Underutilized Option! - Jaiswal, Dushyant; Borle, Firoz; Mathews, Saumya; Mantri, Mayur; Kumar, Vineet; Bindu, Ameya; Yadav, Prabha; Shankhdhar, Vinay Kant (Indian Journal of Plastic Surgery, 2023)
Background The deep inferior epigastric artery perforator (DIEP) flap is a workhorse flap for breast reconstruction. Its use for head and neck (HN) reconstruction is rare. Abdomen provides a donor site abundant in skin and subcutaneous tissue, amenable to primary closure; sizeable, robust, and consistent perforators and a long, sizeable pedicle for comfortable microvascular anastomosis. Its offers all the donor variables needed for HN reconstruction in abundance.Methods It is a quasiexperimental design study. DIEP flap use for HN reconstruction in our series was opportunistic, that is, when donor site matched the defect. Cases that had very thick thighs and lesser bulk in abdomen and cases that had very thin thighs but much more bulk in abdomen were considered for reconstruction using DIEP flap.Results The DIEP flap was done in 11 cases for HN reconstruction. There were two re-explorations during postoperative period: one flap loss and another had partial necrosis.Conclusion Abdomen is an excellent donor site option for HN reconstruction in selected cases, especially when harvested as a perforator flap.
Keywords: DIEP flap; HN reconstruction; large defects; musculocutaneous rectus abdominis flaps